PENERAPAN METODE KARYAWISATA DALAM MENINGKATKAN KEMAMPUAN MENULIS PUISI PADA MAHASISWA PENDIDIKAN GURU SEKOLAH DASAR UNIVERSITAS BORNEO TARAKAN - Ady Saputra (Universitas Borneo Tarakan, 2019)
Abstract: Indonesian Language Skills students can be fostered through listening, speaking, reading and writing. The aim to be achieved is to tryto make students as scientists and professionals who have an attitudetowards Indonesian language and literature, especially skilled in writingpoetry. This research was conducted to find out whether the applicationof effective field trips to produce products in the form of poetry in thelectures of Indonesian Elementary Language and Literature Education.This research is a Classroom Action Research (CAR) conducted in twocycles. Each cycle consists of four stages: (1) planning, (2) the stage ofimplementation, (3) the stage of observation and interpretation, and (4)the stage of analysis and reflection. Increasing the ability to writestudent poetry can be seen from the percentage during theimplementation of the action by 39 (90.6%) students, while as many as 4(9.30%) other students did not experience an increase during the action.